2000
DOI: 10.1002/1522-7219(200006)9:2<67::aid-icd209>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Parent-infant co-sleeping: fathers' roles and perspectives

Abstract: Dyadic co-sleeping (mother -baby) is a common strategy for night-time infant care in the majority of world cultures. Triadic co-sleeping (mother -father -baby) is less common, although still widely practised cross-culturally. This paper examines triadic co-sleeping in an opportunistic sample of parents from the North Tees region of England, and explores fathers' expectations and experiences of sleeping with their babies. Using a prospective study design, 36 sets of parents, pre-and post-natally, were interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…It is important to note the fact that in Sweden fathers are considered appropriate persons with whom children share bed space. The cross‐cultural evidence would support this finding, although the reasons and meaning given for the practice differ (35). ‘Fathering is a feminist issue (36); by using the window of the practice of co‐sleeping to view ideas about gender, as well as the larger paradigm of gender and health (37) it is clear that in Sweden, parents value fathers’ involvement in the practice’.…”
Section: Discussionmentioning
confidence: 89%
“…It is important to note the fact that in Sweden fathers are considered appropriate persons with whom children share bed space. The cross‐cultural evidence would support this finding, although the reasons and meaning given for the practice differ (35). ‘Fathering is a feminist issue (36); by using the window of the practice of co‐sleeping to view ideas about gender, as well as the larger paradigm of gender and health (37) it is clear that in Sweden, parents value fathers’ involvement in the practice’.…”
Section: Discussionmentioning
confidence: 89%
“…The first twenty years of anthropological infant sleep research was therefore dominated by a bioanthropology and evolutionary medicine perspective that revealed: an intricate interrelationship between mother–infant sleep contact and nighttime breastfeeding behavior (McKenna and Bernshaw ; McKenna, Mosko, and Richard ; Mosko, Richard, and McKenna ) the mutual physiological regulation of mother–infant sleep architecture during sleep contact (Mosko et al. ; Mosko, Richard, and McKenna , ) an appreciation of the variability of sleep ecology within UK families and the (often hidden) prevalence of social sleep arrangements (Ball 2006c; Ball, Hooker, and Kelly ; Blair and Ball ) an understanding of the wide range of motivations for and circumstances of different parent–infant sleeping arrangements (Ball , , ; Ball, Hooker, and Kelly ) …”
Section: Contextual Background—a Brief Overview 1987–2007mentioning
confidence: 99%
“… 23 , 24 The majority of infant sleep literature, and specifically literature on bed-sharing prevention, focuses on mothers with less attention given to the beliefs/behaviors of fathers. 11 , 14 , 25 , 26 Fathers are involved in bed-sharing, and yet we know little about the dyadic decision-making process that takes place between couples about infant sleep. 25 Although overnight infant caregiving is conducted mostly by mothers, fathers are often involved in putting infants to sleep and soothing them after nighttime wakening.…”
Section: Incorporating Fathers In Research On Bed-sharingmentioning
confidence: 99%
“… 11 , 14 , 25 , 26 Fathers are involved in bed-sharing, and yet we know little about the dyadic decision-making process that takes place between couples about infant sleep. 25 Although overnight infant caregiving is conducted mostly by mothers, fathers are often involved in putting infants to sleep and soothing them after nighttime wakening. 27 , 28 Furthermore, in an Australian study, mothers reported frequent negotiation of bed-sharing arrangements with the fathers.…”
Section: Incorporating Fathers In Research On Bed-sharingmentioning
confidence: 99%